Small And Medium Enterprises Training For Survival In A Competitive World - Caroline, Ndiritu; Anne, Ndiritu; Harriet, Kidombo (European Scientific Journal, ESJ, 2016)
This study explored the influence of Total Quality Management practices on performance of Small and Medium Enterprises. Youth Projects in Kajiado County, Kenya were used as the target population. One of the key TQM management practices is training of employees. The study sort to determine the influence of training of employees on performance on SMEs. The study was carried out on 168 youth group projects in Kajiado County.Questionnaires and interviews were used as research instruments. For triangulation purpose, the interview schedule was used to confirm the information captured by the questionnaire. Data was collected from both primary and secondary sources. The study used mixed method approach in the collection and analysis, to capture both the qualitative and quantitative data.Spearman’s correlation was used to test the relationship between training and performance of SMEs. The analyses indicated a moderately positive relationship between training and performance of SMEs in Kajiado county which was statistically significant rs=0.400, p=0.600.Based on the findings and conclusions of the study, it is recommended that to improve the performance of the youth groups, they should strive to ensure their product in the market is superior. This can only be ensured by equipping their employees with proper skills, knowledge and values through training.